CHILDBIRTH PREPARATION EFFORTS FOR PREGNANT WOMEN WITH HYPERTENSION AGAINST INCIDENTS OF CHILDBIRTH DIFFICULTIES AT THE CLINIC PRATAMA JALA HUSADA DISKES LANTAMAL V SURABAYA - Hastiniah (Master of Public Health Program Universitas STRADA Indonesia, 2023)
mpanied by complications in pregnancy, one of which is hypertension in pregnant women, so preparation is needed in facing childbirth. The aim of this study was to analyze the effect of childbirth preparation in pregnant women with hypertension on the incidence of birth complications at the Pratama Jala Husada Diskes Lantamal V Surabaya Clinic. This research uses design was correlational analytics with cross sectional approach. The population in this study was 35 respondents with a sample size of 32 respondents. The sampling technique used in this research was accidental sampling. Data collection by using questionnaires and medical records. Data analysis to see the relationship between the independent variable and the dependent variable uses statistical tests chi square with a significant level of α = 0.05. The research results showed that of the 32 respondents, almost half of the respondents prepared well for the delivery of hypertensive pregnant women, namely 15 respondents (46.9%). The majority of respondents did not experience any complications in childbirth, namely 26 respondents (81.2%). Results of data analysis using statistical tests Chi Square The P value was obtained < α 0.05 (0.000 < 0.05), which means that there is an influence of preparation for childbirth in pregnant women with hypertension on the incidence of complications in childbirth at the Clinic Pratama Jala Husada Lantamal V Surabaya, this is due to good childbirth preparation for pregnant women. an important role in carrying out early management to prevent complications that complicate childbirth. The conclusion of this study is that good preparation for childbirth for hypertensive pregnant women means that pregnant women do not experience complications during childbirth.